Current Situation of Digital Agriculture in Egypt - (ICARDA), International Center for Agricultural Research in the Dry Areas (2024)
This report highlights various aspects of digital transformation in Egypt, starting with an overview of 8 categories of digital agriculture tools, of which only sensors and mobile apps are fairly widely used in Egypt. Various privately produced apps are available at no or low cost, while government apps such as Al Mufeed, Hudhud (extension services tools), and DAIRS (climate early warning) are also under development. Mobile connectivity, data security concerns and knowledge levels of farmers are important constraints on further adoption of DA tools by SME, as are the more recent high inflation and price surges. While persistent commercial market conditions and inflation may be harder to solve, constraints can be alleviated on the e-Extension system that communicates, creates, stores, disseminates and manages agricultural information, enhances skills and capabilities, and creates links between agricultural and rural development stakeholders.